PERAN LEMBAGA PERLINDUNGAN PEREMPUAN DALAM MEMBERIKAN PERLINDUNGAN TERHADAP KORBAN KDRT - Sukarno, Sukarno (Fakultas Hukum Universitas Nahdlatul Wathan Mataram, 2020)
Violence against women lately has been widely discussed in the form of workshops,seminars, discussions and public dialogues. The organizers consisted of various groups bothfrom government, non-government organizations and academics. The formulation of theproblems raised in this study are: (1) What is the form of legal protection for victims ofdomestic violence according to Law Number 23 of 2004; (2) What is the role of women'sprotection institutions in providing protection to victims of domestic violence; This studyexamines the subject matter through a normative juridical approach which is examining theregulations regarding the Role of the Women's Protection Agency in providing protection tovictims of domestic violence according to Law Number 23 of 2004 concerning theelimination of violence in household. The conclusion in this study is the Law on theElimination of Domestic Violence was born to save victims of crime in the household. This isa good sign for those victims of domestic violence because they can carry out prosecutionsand are legally protected. Forms of victim protection, providing legal education with genderequality, assistance in the legal process, and the role of women's protection institutions, legalaid institutions, and the role of the government in fighting for the emancipation of women ofgender equality.